PENINGKATAN KAPASITAS PENGURUS MELALUI PENYUSUNAN RENCANA KERJA DAN RAPB KOPERASI PADA KOPERASI BERBAGAI SEKTOR DI KOTA BAUBAU - Tri Pratiwi, Endang; Jasiyah, Rabiyatul; Suriadi, Suriadi; Malik, Ernawati; Abdullah, La Ode Dedi; Abdullah, Rudi (Jurnal Pengabdian Masyarakat Berkarya, 2025)
The purpose of community service activities is to increase the capacity of the management in the form of understanding and skills about the importance of planning and budgeting in cooperative management, as well as providing practical knowledge about the steps for preparing a good and correct work plan and RAPB. This activity is designed using adult learning principles, which emphasize experience, relevance, and active involvement of participants in the learning process. The training activities for the preparation of cooperative work plans and RAPBs for cooperatives in various sectors in Baubau City in 2023 were well implemented and achieved the expected objectives, namely gaining a better understanding of the basic principles of cooperative planning and budgeting, as well as practical techniques in preparing effective work plans and RAPBs as contained in the Cooperative Work Plan and RAPB learning module during the training. In addition, the participants also gained insight into cooperative management through exchanging experiences and best practices with fellow cooperative administrators and members.